Evaluation of Antibacterial and Anti-Malaria Potential of Wonderful Kola (Buchiolizia coreica) Seed Extract in Male Wister Rats - Umar, Kerenhappuch Isaac; Tansaba, Akafa Andes; Ugoeze, Egeonu Stephen; Nanmar, Chakfa; Umaru, Isaac John (Darul Yasin Al Sys, 2024)
One of the areas for the search for new antimalarial drugs is from the claimed antimalarial plants from the African flora. Only few of these claims have been authenticated by scientific investigation. Plants form the major part of treatments used by traditional healers in many societies, Bucholzia Coricea (B. Coriacea) a perennial plant belonging to the family capparidaceae and genus Bucholzia is popularly known as wonderful kola. Earlier studies carried out on different parts of this plant shows that it has great medicinal potentials thus, the evaluation of antibacterial and anti-malaria potential of wonderful kola (Bucholzia Coricea) seed extract in male Wister rats. Material and Methods: Fresh seeds of B. coricea were plucked and washed with distilled water, concentrated using rotary evaporator. Standard antibacterial agent (30 μg) tetracycline, antimicrobial susceptibility test discs and Nutrient agar was used. 100g of crude extract taken into a conical flask, the crude extracts were tested by disc diffusion method on nutrient agar medium. selected bacteria were used to evaluate the antibacterial activities of the crude extracts of Bucholizia Coricea seed, Escherichia coli (ATCC©25922), Salmonella typhi, (ATCC©14028), Staphylococcus aureus (ATCC©25923) and Kliebselia pneumonia, (ATCC©19155). A total of seventy-eight Swiss albino mice (18-25 g) of both sexes were used in the study. Eighteen for acute toxicity study while thirty were used for each of the in vivo antiplasmodial test. Results: antibacterial; higher inhibition was observed at 400µg/mL on Klebsiella pneumonia at 15.14 + 0.07mm when compared to standard 21.19+ 0.03mm. while the curative effect of the extract in P. berghei infected rats at 40mg/kg show significant parasitaemia density to be 30.98+4.30 and pre(D3) was 2.90+0.11mm** with survival time at post (D7) to be 29.67+0.21mm when compared to CQ as standard drug control with 10mg/kg. Conclusion: This study has however stablished the rationale for the traditional use of this plant in Nigeria and like many others, proved that medicinal plants which have folkloric reputations for anti-bacterial and antimalarial properties, thus, as an agent.